Knowledge of Adolescent Post Partum Mothers About Umbilical Cord Care - Nur Fadillah Pratama Yusuf; Ika Wulansari; Lintje Boekoesoe (Jambura Nursing Journal, 2023)
Umbilical cord care is an action to treat the umbilical cord in newborns to keep it dry and prevent infection. This study aims to determine the level of knowledge of adolescent post partum toward umbilical cord care. This study employs a quantitative method with a descriptive design. The populations are adolescent post partum in the working area of Kota Timur Public Health Center, totaling 98 people with a total sample of 79 people who are determined using the Cluster Random Sampling technique, The research questionnaire used a mother's knowledge questionnaire about cord care which consisted of 26 questions and the data used are univariate data. The results show that the number of respondents who have good knowledge is 32 respondents (40,5%), 40 respondents (50,6%) have sufficient knowledge, 7 respondents (8,9%) have a lack of knowledge.